Situating Expertise: Lessons from the HIV/AIDS Epidemic. Issue 9 (19th June 2018) - Paremoer, Lauren
Abstract: How do Scientific Advisory Committees (SACs) frame the relationship between political agency and expertise in their work? What are the political implications of the ways in which SACs legitimate or obscure specific forms of political agency? Using a South African case study, human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome (AIDS) activists' participation in clinical trials designed to demonstrate the efficacy of highly active antiretroviral treatment (HAART) in resource‐poor settings, and the process of translating scientific knowledge about HIV/AIDS into public policy under the leadership of a SAC, the South African National AIDS Council (SANAC), is analyzed. The case study suggests that 1) political agency plays a significant role in generating and disseminating scientific data that allow activists to fulfill their political goals; 2) SACs primarily value political agency as a resource for implementing their prescriptions and legitimating their work; 3) processes of political conscientization, movement building, democratic collective action, and deliberation can contribute to the reliability and validity of the technical knowledge SACs rely on, and under some circumstances, contribute to the political resonance their recommendations have with impacted constituencies; and 4) social theory can serve as a resource for negotiating conflicts between technical experts and activists that cannot be settled by appealing to clinical facts. Abstract : Using case study evidence from human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome (AIDS) activism in South Africa, this article argues that Scientific Advisory Committees (SACs) primarily value political agency as a resource for implementing their prescriptions and legitimating their work. However, processes of political conscientization, movement building, democratic collective action, and deliberation can also contribute to the reliability and validity of the technical knowledge SACs rely on.